Gambaran Usia dan Stadium Klinis Pasien Kanker Payudara yang dilakukan Pemeriksaan Imunohistokimia di Rumah Sakit Abdul Wahab Sjahranie pada Tahun 2018 - Yulianto, Ade Yusuf; Irawiraman, Hadi; Ompusunggu, P.M.T. Mangalindung (Jurnal Kebidanan Mutiara Mahakam, 2020)
ABSTRACKBreast cancer still occupies the highest incidence of all types of malignancies in women. Based on data recorded at Abdul Wahab Sjahrenie Hospital, 200 new cases are found each year. Immunohistochemical profile examination has been used extensively as a basis for classifying breast cancer molecularly. Expression of hormone receptors (ER, PR) and HER-2 found in immunohistochemical examinations are useful for determining therapeutic options that fit the patient's needs. The purpose of this descriptive study was to determine the characteristics of the immunohistochemical profile of breast cancer patients in Abdul Wahab Sjahranie Regional Hospital Samarinda in the January-December 2018 period based on age and clinical stage that had been examined by immunohistochemical examination including the expression of ER PR, Ki-67 and HER2. Method: This study used a cross-sectional descriptive study design by taking secondary data from breast cancer patients who had performed immunohistochemical examinations at Abdul Wahab Sjahranie Regional Hospital Samarinda in the January 2018 - December 2018 period. From 479 breast cancer patients came to Abdul Wahab Regional Hospital Sjahranie Samarinda, only 177 (37.18%) patients did immunohistochemical examinations. Most patients aged 40-49 were 65 patients (36.7%) had breast cancer, the highest clinical stage IIIB with 92 cases (52%), the Ki-67 with severe highest interpretation, range> 30% with 73 patients (41.2%), more positive ER than negative, in 93 patients (52.5%), while negative examination results 84 patients (47.5%). PR is the same as ER, which is 96 patients (54.2%), while negative examination results are 81 patients (45.8%). Most HER-2 results were negative, in 109 patients (61.6%). In this study the highest number of cases of breast cancer patients ranged between the ages of 40-49 years and at least aged 70 years and above. The clinical stage is most often found in stage IIIB (advanced). Ki-67 examination was found most frequently in severe interpretations. Examination of estrogen receptors is found to be most widely in positive interpretation. Positive progesterone tests to be most widely than negative examinations. Her-2 examination was found to be most widely in negative interpretation Keywords: Immunohistochemical examination, Hormone receptors, HER-2, Clinical Stadium